2021
DOI: 10.1016/j.ymeth.2021.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Multi-targeting approach for nsp3, nsp9, nsp12 and nsp15 proteins of SARS-CoV-2 by Diosmin as illustrated by molecular docking and molecular dynamics simulation methodologies

Abstract: Novel coronavirus SARS-CoV-2 continues to spread rapidly worldwide and causing serious health and economic loss. In the absence of any effective treatment, various in-silico approaches are being explored towards the therapeutic discovery against COVID-19. Targeting multiple key enzymes of SARS-CoV-2 with a single potential drug could be an important in-silico strategy to tackle the therapeutic emergency. A number of Food and Drug Administration (FDA) approved drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Molecular docking study of ivermectin, and remdesivir indicates spike, M, N, nsp14, and nsp16 as viable targets for drug treatment development of SARS-CoV-2 81 , 82 , while Raltegravir and Maraviroc are potential candidates to inhibit nsp-16 protein 83 . Multi-targeting features of Diosmin display highest binding affinity and inhibitory action of several non-structural proteins (nsp3, nsp9, nsp12, nsp15) 84 . This confirmation of the role of non-structural proteins in treatment validates our target proteins predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking study of ivermectin, and remdesivir indicates spike, M, N, nsp14, and nsp16 as viable targets for drug treatment development of SARS-CoV-2 81 , 82 , while Raltegravir and Maraviroc are potential candidates to inhibit nsp-16 protein 83 . Multi-targeting features of Diosmin display highest binding affinity and inhibitory action of several non-structural proteins (nsp3, nsp9, nsp12, nsp15) 84 . This confirmation of the role of non-structural proteins in treatment validates our target proteins predictions.…”
Section: Discussionmentioning
confidence: 99%
“…The repurposing potential of 34 bioactive terpenes and their derivatives to Mpro and PLpro was also predicted by docking and MM/PBSA calculations . Other MM/PB­(GB)­SA-based drug repurposing works considering two or more targets include studies in the literature. …”
Section: Methods and Approachesmentioning
confidence: 99%
“…The nsp9 is single-strand RNA-binding protein of SARS-CoV (nsp9–SARS) which was found to be essential for viral replication ( Frieman et al, 2012 ). nsp9 of SARS-CoV-2 can bind to the nidovirus RdRp-associated nucleotidyltransferase (NiRAN) domain relating the viral replication and transcription ( Kumar M. et al, 2021 ), and it was also considered to be the therapy target for COVID-19 treatment ( Zhang et al, 2020 ; Kumar et al, 2021b ). There were several studies to screen the potential candidate compounds to bind or act on nsp9 by in silico tools ( Barros et al, 2020 ; Chandra et al, 2021 ; Junior et al, 2021 ), and one in vitro cellular assay showed the inhibition on nsp9 can reduce the viral replication of SARS-CoV-2 ( Littler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There were several studies to screen the potential candidate compounds to bind or act on nsp9 by in silico tools ( Barros et al, 2020 ; Chandra et al, 2021 ; Junior et al, 2021 ), and one in vitro cellular assay showed the inhibition on nsp9 can reduce the viral replication of SARS-CoV-2 ( Littler et al, 2021 ). The molecular docking results showed that curcumin can bind to the ligand binding site of nsp9, and curcumin can form about 11 interaction sites with nsp9 ( Kumar et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%